Controlled oligomerization of [1.1.1]propellane through radical polarity matching: selective synthesis of SF5- and CF3SF4-containing [2]staffanes - Buldt, Jón Atiba; Kong, Wang-Yeuk; Kraemer, Yannick; Belsuzarri, Masiel M.; Patel, Ansh Hiten; Fettinger, James C.; Tantillo, Dean J.; Pitts, Cody Ross (Beilstein Journal of Organic Chemistry, 2024)
Selectivity in radical chain oligomerizations involving [1.1.1]propellane – i.e., to make [n]staffanes – has been notoriously challenging to control when n > 1 is desired. Herein, we report selective syntheses of SF5- and CF3SF4-containing [2]staffanes from SF5Cl and CF3SF4Cl, demonstrating cases whereby oligomerization is preferentially truncated after incorporation of two bicyclopentane (BCP) units. Synthetic and computational studies suggest this phenomenon can be attributed to alternating radical polarity matching. In addition, single-crystal X-ray diffraction (SC-XRD) data reveal structurally interesting features of the CF3SF4-containing [2]staffane in the solid state.
Keywords: pentafluorosulfanylation; [1.1.1]propellane; radical chain oligomerization; staffanes; strain-release